햅틱 장치의 프로파일 측정 및 감성 평가 - 전차수; 추헌성; 박세형; 김래현; 신상균 (한국CDE학회, 2010)
Developed in this research is a TP (tangible prototyping) system, which consists of two modules; (1) a virtual reality model to evaluate the functions and appearance of the product, and (2) a haptic device to emulate tactile and kinesthetic properties of mechanical dial knobs. As an example, a washing machine is modeled using a commercial CAD system and transformed in VRML and X3D formats. Some dynamic behaviors and kinematic characteristics are programmed using X3D script and Java. Various haptic behaviors of the dial are generated by modulating torque profile according to the rotation angle. A torque profile measuring system is developed to evaluate the behaviors of the haptic dial physically. Haptic sensibility evaluations are accomplished using the TP by semantic differential method.